Підвищення ефективності електронно-променевого плавлення металу в гарнісажному тиглі - Гориславець, Ю. М.; Глухенький, О. І.; Бондар, О. І.; Ладохін, С. В.; Ворон, М. М.; Ліхацький, Р. Ф. (Physico-technological Institute of Metals and Alloys, 2023)
The paper considers the issues of increasing the efficiency of electron beam scull melting (EBSM) by optimizing the parameters of electromagnetic stirring (EMS) of the melt. The example of titanium melt preparation process in a copper watercooled sectional crucible is shown on example of an EMS system consisting of two coils. The analysis of melting and casting technological parameters, as well as modeling of temperature and hydrodynamic processes, are reviewed. The optimum parameters of a liquid metal bath in the formed volume of metal inside the scull are determined, after which the most effective growth of the liquid metal amount could be achieved. The expediency of increasing the efficiency of electromagnetic stirring by controlling the phase shift angle between the electrical voltages fed by the adjacent coils of the crucible electromagnetic stirring system is shown. It has been determined and shown that in the process of melt bath forming, it is advisable to change its motion directions at different stages of the process. The conditions of the highest energy efficiency of the melting process, which are to maintain a moderate thickness of the scull side walls, are investigated. This feature is up to reduce the heat dissipation from the melt and also to reduce the intensity and the area of evaporation of the metal under the action of electron beam. This approach also improves the lifetime of the crucible and reduces the risk of accidents. The possibility of reducing the melting time by introducing into the crucible a fixed mass of the melt obtained in another melting tank after preheating the charge with an electron beam to a temperature at which the explosive emission of the melt is eliminated is considered.